Cavernous Sinus Involvement by Pituitary Adenomas: Clinical Implications and Outcomes of Endoscopic Endonasal Resection - Ajlan, Abdulrazag; Achrol, Achal S.; Albakr, Abdulrahman; Feroze, Abdullah H.; Westbroek, Erick M.; Hwang, Peter; Harsh, Griffith R., IV (Journal of Neurological Surgery Part B: Skull Base, 2017)
Background Parasellar invasion of pituitary adenomas (PAs) into the cavernous sinus (CS) is common. The management of the CS component of PA remains controversial.Objective The objective of this study was to analyze CS involvement in PA treated with endoscopic endonasal approaches, including incidence, surgical risks, surgical strategies, long-term outcomes, and our treatment algorithm.Methods We reviewed a series of 176 surgically treated PA with particular attention to CS involvement and whether the CS tumor was approached medial or lateral to the internal carotid artery.Results The median duration of follow-up was 36 months. Macroadenomas and nonfunctional adenomas represented 77 and 60% of cases, respectively. CS invasion was documented in 23% of cases. CS involvement was associated with a significantly diminished odds of gross total resection (47 vs. 86%, odds ratio [OR]: 5.2) and increased the need for subsequent intervention (4 vs. 40%, OR: 14.4). Hormonal remission was achieved in 15% of hormonally active tumors. Rates of surgical complication were similar regardless of CS involvement.Conclusion Our tailored strategy beginning with a medial approach and adding lateral exposure as needed resulted in good outcomes with low morbidity in nonfunctional adenomas. Functional adenomas involving the CS were associated with low rates of hormonal remission necessitating higher rates of additional treatment.
Keywords: endoscopic; cavernous sinus; pituitary adenomas